The Impact of Digitally-Integrated Coloring Tasks on The Development of Fine Motor Proficiencies in Early Childhood Education Settings - Razin, Muhammad; Zelpia, Riri; Barton, Gertude (CV. INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: This study investigated the effects of digitally-integrated coloring tasks compared to traditional paper-based coloring activities on the development of fine motor skills in preschool children. Materials and methods: A quasi-experimental study was conducted over an 8-week period with 60 preschool children (aged 4-5 years) from four early childhood education centers in Kabupaten Kampar, Riau, Indonesia. Participants were randomly assigned to either an experimental group using tablet-based coloring applications (n=30) or a control group using traditional paper-based coloring materials (n=30). Fine motor skills were assessed using the Peabody Developmental Motor Scales-Second Edition (PDMS-2) and the Beery-Buktenica Developmental Test of Visual-Motor Integration (Beery VMI). Results: Both groups showed improvements in fine motor skills, but the experimental group demonstrated significantly greater gains in visual-motor integration (p<0.05) and grasping skills (p<0.05) compared to the control group. Effect sizes indicated a medium to large impact of the digital intervention on fine motor development. Conclusions: Digitally-integrated coloring tasks can effectively enhance fine motor proficiencies in early childhood, particularly in visual-motor integration and grasping skills. These findings suggest that thoughtfully implemented digital tools may serve as valuable supplements to traditional methods in early childhood education settings.